The Influence of The School Principal's Leadership Style and Empowerment Through Motivation on Teacher Participation in The Sekolah Penggerak Program - Iswahyudi; Harsono; Suyatmini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
One of the efforts to improve the quality of 21st-century learning is the Driving School Program. There are several obstacles in running the program, including low teacher participation. Teacher participation can be influenced by the principal's leadership style, empowerment, and teacher motivation. This study aims to analyze the influence of the principal's leadership style and empowerment through motivation on teacher participation in the driving school program. This type of research is correlational with a quantitative approach. The subjects of this study were principals and teachers of public high schools undergoing the driving school program in Boyolali. Data were collected using a questionnaire through a Google form supported by observation and documentation. Data were analyzed with PLS (Partial Least Square) through SmartPLS software. The data processing results show a significant influence between the Principal's Leadership Style through the intervening variable of Teacher Motivation on Participation. There is a substantial influence between empowerment through motivation and Teacher Participation. The results of the data analysis show that the hypothesis is accepted. The Teacher Motivation variable has a medium-high influence in mediating the Principal Leadership Style variable on the teacher Participation variable with a statistical value of upsilon (v) mediation effect of 0.0137. Teacher Motivation has a medium influence in mediating the Empowerment variable on Teacher Participation.